2014
DOI: 10.1016/j.jshs.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Principles and practices of training for soccer

Abstract: The complexity of the physical demands of soccer requires the completion of a multi-component training programme. The development, planning, and implementation of such a programme are difficult due partly to the practical constraints related to the competitive schedule at the top level. The effective planning and organisation of training are therefore crucial to the effective delivery of the training stimulus for both individual players and the team. The aim of this article is to provide an overview of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 27 publications
3
93
1
5
Order By: Relevance
“…Unlike the results of the current study, Kondrič et al [58] showed that recreational football leads to meaningful increase of lean mass and a major part of this increase is due to the lean mass of lower limbs. This is probably due to the necessity of this attribute in the lower limbs for football [59]; however, this is not necessary for success in table tennis [58].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the results of the current study, Kondrič et al [58] showed that recreational football leads to meaningful increase of lean mass and a major part of this increase is due to the lean mass of lower limbs. This is probably due to the necessity of this attribute in the lower limbs for football [59]; however, this is not necessary for success in table tennis [58].…”
Section: Discussionmentioning
confidence: 99%
“…Male soccer players are the most investigated population of athletes in sport sciences [41]. Soccer is a high-intensity sport that involves complex movement patterns and that is characterized by an intermittent activity profile [36]. The alternation of walking, jogging, high-intensity running, and sprinting requires the contribution from both the aerobic and the anaerobic energy systems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one, two and three competitive fixtures can be scheduled within a relatively short period (e.g. 6-8 days) (Morgans, Orme, Anderson, & Drust, 2014). This intensive competitive schedule can place restrictions on time and thus impact the planning and implementation of training and match preparation (e.g.…”
Section: Introductionmentioning
confidence: 99%